The effectiveness of utilizing output details in evaluation of government work plans 2023 - Rani Dewi (Jurnal Geuthèë: Penelitian Multidisiplin, 2023)
The implementation of the 2023 RKP is based on Presidential Regulation Number 134 of 2022 concerning Updating the Government Work Plan for 2023; which contains 7 National Priorities (PN). Specifically in Appendix 2 of the 2023 RKP National Development Matrix, the Ministry of PUPR supports a number of 6 PNs. In this matrix, the PN is described with its targets, indicators, targets and funding allocation as well as the implementing agencies involved. Since 2020, the Ministry of National Development Planning/Bappenas and the Ministry of Finance have implemented the use of KRO/RO in the budgeting system. Output Detailed (OD) is a very specific real output that is produced which focuses on the characteristics of each unit and is directly related to the tasks and functions of the work unit in supporting the achievement of predetermined activity targets. The 2023 RKP evaluation was carried out primarily to measure the results of development performance achievements. Since the implementation of OD, evaluations have also been carried out using the RO approach. At the Ministry of PUPR, with a total of 37,850 packages, OD codification is carried out in a more generic manner. This makes the use of OD ineffective in evaluating the achievements of the 2023 PN RKP Development Matrix.